How countries count crime: an exercise in police discretion - Eterno, John; Verma, Arvind; Silverman, Eli B. (Routledge, 2023)
Introduction / John A. Eterno, Arvind Verma, and Eli B. Silverman -- 1. Collecting police-recorded data in Austria: a review of the current state of play / Stefanie Meyer -- 2. How France counts crime: a shared interest in bad accounts / Christian Mouhanna -- 3. Counting crime in the Isle of Spice: a review of the Royal Grenada Police Force / Christine Sharon Barrow -- 4. Counting crime: an exercise in police discretion report from India / Arvind Verma and Asim Arun -- 5. Role of police in the compilation of crime data in Mexico / Elena Azaola and Cliff Roberson -- 6. Crime statistics: to measure is to know, but do more with less / Peter Versteegh and René Hesseling -- 7. The challenges of police discretion and crime statistics in Nigeria / Abdulrahman Dambazau -- 8. How Portugal counts crime: an exercise in police discretion / Gonc̦alo de Melo Bandeira and Paulo Teixeira -- 9. The state and trends of crime in modern Russia / Yakov Gilinskiy -- 10. Counting crime in South Africa / Gareth Newham -- 11. Police data in Spain: still a grey landscape / Francesc Guillén Lasierra and Santiago Herrero Blanco -- 12. Crime reporting in Sweden / Stefan Holgersson -- 13. Measuring crime and victimization rates in Tanzania / Simeon P. Sungi -- 14. A web of deceit: police crime statistics of England and Wales / Rodger Patrick -- 15. Crime reporting in the United States: truth or consequences / John A. Eterno and Eli B. Silverman.